2019
DOI: 10.3390/hydrology6020032
|View full text |Cite
|
Sign up to set email alerts
|

Can a Calibration-Free Dynamic Rainfall‒Runoff Model Predict FDCs in Data-Scarce Regions? Comparing the IDW Model with the Dynamic Budyko Model in South India

Abstract: Construction of flow duration curves (FDCs) is a challenge for hydrologists as most streams and rivers worldwide are ungauged. Regionalization methods are commonly followed to solve the problem of discharge data scarcity by transforming hydrological information from gauged basins to ungauged basins. As a consequence, regionalization-based FDC predictions are not very reliable where discharge data are scarce quantitatively and/or qualitatively. In such a scenario, it is perhaps more meaningful to use a calibrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 80 publications
(137 reference statements)
0
3
0
Order By: Relevance
“…However, these catchments may have partial or fully available climate records at various locations within and around them. In such cases where data is scarce or unavailable, the hydrologists have developed models and techniques which do not require the availability of long time series of meteorological and hydrological observations (Loukas and Vasiliades, 2014;Blöschl et al, 2013;Botero and Francés, 2010;Nag and Biswal, 2019;Post, 2004). Depending on whether flow hydrographs, statistics or quantiles are the required outputs, several methods can be used including rainfall-runoff modelling using global parameters transfer, quantile estimation from empirical methods and time series summaries from flow duration curves (FDC) regional equation (Swain and Patra, 2017;Valimba, 2016;Loukas and Vasiliades, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, these catchments may have partial or fully available climate records at various locations within and around them. In such cases where data is scarce or unavailable, the hydrologists have developed models and techniques which do not require the availability of long time series of meteorological and hydrological observations (Loukas and Vasiliades, 2014;Blöschl et al, 2013;Botero and Francés, 2010;Nag and Biswal, 2019;Post, 2004). Depending on whether flow hydrographs, statistics or quantiles are the required outputs, several methods can be used including rainfall-runoff modelling using global parameters transfer, quantile estimation from empirical methods and time series summaries from flow duration curves (FDC) regional equation (Swain and Patra, 2017;Valimba, 2016;Loukas and Vasiliades, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…They reported that the catchment runoff response similarity (CRRS) approach outperformed the other commonly used regionalization approaches for reproducing the desired hydrograph in the ungauged watersheds. Moreover, it has been reported that the performance of regionalization methods often influenced by the streamflow gauging station density (Müller, Thompson, & Sciences, ; Nag & Biswal, ; Oudin, Andréassian, Perrin, Michel, & Le Moine, ; Tegegne & Kim, ). However, Tegegne and Kim () reported the capability of the CRRS approach in different basins in terms of climate condition and stream gauging station network density.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been reported that the performance of regionalization methods often influenced by the streamflow gauging station density (Müller, Thompson, & Sciences, 2016;Nag & Biswal, 2019;Oudin, Andréassian, Perrin, Michel, & Le Moine, 2008;Tegegne & Kim, 2018).…”
Section: Introductionmentioning
confidence: 99%